Cost‐effectiveness of a nurse practitioner‐family physician model of care in a nursing home: controlled before and after study. (27th April 2016) - Lacny, Sarah; Zarrabi, Mahmood; Martin‐Misener, Ruth; Donald, Faith; Sketris, Ingrid; Murphy, Andrea L.; DiCenso, Alba; Marshall, Deborah A.
Abstract: Aims: To examine the cost‐effectiveness of a nurse practitioner‐family physician model of care compared with family physician‐only care in a Canadian nursing home. Background: As demand for long‐term care increases, alternative care models including nurse practitioners are being explored. Design: Cost‐effectiveness analysis using a controlled before‐after design. Methods: The study included an 18‐month 'before' period (2005–2006) and a 21‐month 'after' time period (2007–2009). Data were abstracted from charts from 2008–2010. We calculated incremental cost‐effectiveness ratios comparing the intervention (nurse practitioner‐family physician model; n =  45) to internal ( n =  65), external ( n =  70) and combined internal/external family physician‐only control groups, measured as the change in healthcare costs divided by the change in emergency department transfers/person‐month. We assessed joint uncertainty around costs and effects using non‐parametric bootstrapping and cost‐effectiveness acceptability curves. Results: Point estimates of the incremental cost‐effectiveness ratio demonstrated the nurse practitioner‐family physician model dominated the internal and combined control groups (i.e. was associated with smaller increases in costs and emergency department transfers/person‐month). Compared with the external control, the intervention resulted in a smaller increase in costs and larger increase in emergency department transfers. Using a willingness‐to‐pay threshold of $1000 CAD/emergency department transfer, the probability the intervention was cost‐effective compared with the internal, external and combined control groups was 26%, 21% and 25%. Conclusion: Due to uncertainty around the distribution of costs and effects, we were unable to make a definitive conclusion regarding the cost‐effectiveness of the nurse practitioner‐family physician model; however, these results suggest benefits that could be confirmed in a larger study.